PPAT Responsibilities That Do Not Issue the Deed of Grant of Guarantee Rights and Position of Creditors in Bankruptcy - MAHAWIRA, Made Dananjaya; ARJAYA, I Made; DHARSANA, I Made Pria (Indonesia Strategic Sustainability, 2023)
Purpose: The action taken is that lending and borrowing are not accompanied by the existence of an item that the debtor guarantees. However, in reality, in banking, there is a provision of a facility from the bank for its customers who do not lend to the debtor without including a guarantee.Methodology: The research method conducted by the author is normative research. The formulation of the problems that will be discussed includes 1. What is the responsibility of the PPAT towards the cover note stating that the Mortgage will be installed? 2. What is the creditor's position in bankruptcy because the mortgage right is not installed by the PPAT? The responsibility of a PPAT for a cover note that has stated the installation of mortgage rights is a criminal responsibility in which the right leads to individual responsibility.Findings: There is an imposition of sanctions either dishonorably dismissed or imposition of an institution for an action carried out by the PPAT and the existence of civil responsibility that provides direction in compensating creditors with the loss of the certificate of ownership.Implication: Judging from the position of a creditor in bankruptcy because the mortgage right is not installed by the PPAT, it is a creditor's position in the event of bankruptcy if it is based on the position of creditors with an equal or equal position. The granting of equal rights from the results of a bankrupt boedel execution has been adjusted to the amount of each bill.